Use of the Intratumoural Anticancer Drug Tigilanol Tiglate in Two Horses - De Ridder, Thomas; Ruppin, Mick; Wheeless, Meagan; Williams, Stephanie; Reddell, Paul (Frontiers in Veterinary Science, 2020)
Tigilanol tiglate is a novel small molecule approved as a veterinary pharmaceutical in Europe for intratumoural treatment of non-metastatic, non-resectable canine mast cell tumours. The drug has a ‘tumour agnostic’ mode of action associated with induction of an acute inflammatory response at the treatment site, immune cell recruitment, and disruption of tumour vasculature. Consequently, tigilanol tiglate has potential in treating a range of tumour types in humans and companion animals. However, it is likely that species-specific dosing and concomitant medication protocols will be required, especially to manage the drug-induced acute inflammatory response at the treatment site. As an initial step in evaluating tigilanol tiglate for treating cutaneous tumours in horses, we developed an equine-specific protocol involving (a) a 30% reduction in intratumoural tigilanol tiglate dose rate compared to that used in dogs, and (b) a regime of concomitant medications to manage the drug-induced acute inflammatory response at the treatment site. Here we report a preliminary study in two horses using the protocol to treat (i) an aggressive fibroblastic sarcoid that had recurred following surgical excision and (ii) a fast-growing peri-ocular squamous cell carcinoma. Clinical response to tigilanol tiglate treatment in these cases was similar to that observed in canine and human patients. Localised inflammation and bruising developed rapidly at the treatment site with haemorrhagic necrosis of the tumour evident within 24 hours. Slough of necrotic tumour mass occurred within 6 to 16 days followed by infill of the tissue defect and full re-epithelialisation of the treatment site with good functional outcome. Drug-induced inflammation and oedema at the treatment site were well controlled by the concomitant medications and largely resolved within 3 days, while the wound that formed following tumour slough healed uneventfully. Both patients displayed minor lethargy during the first 36 hours after treatment and localised treatment-site discomfort was apparent over the first 3 to 5 days. There was no evidence of recurrence of the sarcoid at 93 days, or the squamous cell carcinoma at 189 days. The results from this study support continued development and evaluation of tigilanol tiglate as a potential future treatment option for cutaneous equine tumours.